Критерій для визначення максимального числа копій кожного файла в розподіленій базі даних з копіями - Демидович, О. В.; Цегелик, Г. Г. (Видавництво Національного університету “Львівська політехніка”, 2020)
The problem of optimal allocation of files amongst servers of computer database are considered. Mathematical model for solving this problem is constructed. Criteria for determination of maximum number of copies are proposed.
Keywords: 5І9.68